Anterior interosseous nerve syndrome following infection with COVID-19: a case report - Akira Ikumi; Yuichi Yoshii; Katsuya Nagashima; Yosuke Takeuchi; Masaki Tatsumura; Takeo Mammoto; Atsushi Hirano; Masashi Yamazaki (Journal of Medical Case Reports, 2023)
Abstract Background Various neurological manifestations associated with coronavirus disease 2019 have been increasingly reported. Herein, we report a rare case of anterior interosseous nerve syndrome, which occurred 5 days after the onset of coronavirus disease 2019. Case presentation A 62-year-old Asian woman with a history of coronavirus disease 2019 who developed a complete motor deficit in the left flexor pollicis longus and pronator quadratus without sensory deficits. The symptoms appeared as a sudden onset fatigue and severe pain of the left arm, 5 days after the onset of coronavirus disease 2019. She noticed paralysis of the left thumb at 2 weeks after the onset of coronavirus disease 2019. Electromyography assessment of the anterior interosseous nerve-dominated muscles revealed neurogenic changes such as positive sharp wave and fibrillation in flexor pollicis longus and pronator quadratus, confirming the diagnosis of anterior interosseous nerve syndrome. There were no other diseases that could have resulted in peripheral nerve palsy. We performed a functional reconstruction surgery of the thumb by tendon transfer from the extensor carpi radialis longus to the flexor pollicis longus. The patient reported a good patient-reported outcome (2.27 points in QuickDASH Disability/Symptom scoring and 5 points in Hand20 scoring) at final follow-up (1 year after the surgery). Conclusion This case highlights the need for vigilance regarding the possible development of anterior interosseous nerve syndrome in patients with coronavirus disease 2019. Tendon transfer from extensor carpi radialis longus to flexor pollicis longus can provide good functional recovery for unrecovered motor paralysis after anterior interosseous nerve syndrome.